Impact of PFAS exposure on prevalence of immune-mediated diseases in adults in the Czech Republic - Rudzanova, Barbora; Vlaanderen, Jelle; Kalina, Jiří; Piler, Pavel; Zvonar, Martin; Klanova, Jana; Blaha, Ludek; Adamovsky, Ondrej (Environmental research, 2023)
BACKGROUND: Per- and polyfluoroalkyl substances (PFASs) are emerging environmental contaminants with multiple hazardous properties including immunomodulation potency. Human exposure to PFASs has been associated with various immune-mediated diseases and outcomes. This study aimed to investigate the association between PFAS exposure and immune-mediated diseases such as allergies, eczemas, and autoimmune diseases in a population of adults in the Czech Republic. METHODS: This study included 309 adults from the Central European Longitudinal Study of Parents and Children: Young Adults (CELSPAC: YA). 12 PFASs were measured in participants' serum by HPLC-MS/MS, 3 PFASs were removed from the subsequent analyses due to low detection frequency. The associations of 9 PFASs with 9 immune-mediated diseases were assessed by logistic regression. Furthermore, Bayesian kernel machine regression (BKMR) was used to estimate the effect of the PFAS mixture on immune-mediated diseases. All analyses were adjusted for sex, age, BMI, smoking, education, and family history of immune-mediated diseases. In cases of a statistically significant interaction of PFASs and sex, stratified analyses were performed for men and women. RESULTS: Perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS) were negatively associated with both atopic eczema (OR per IQR increase 0.58 (95% CI 0.37-0.90) for PFOA and 0.56 (0.32-0.95) for PFOS) and contact dermatitis (0.37 (0.16-0.85) for PFOA and 0.33 (0.11-0.94) for PFOS). Perfluoroundecanoate (PFUnDA) was negatively associated with pollen, dust, and mite allergy (0.62 (0.43-0.89)). BKMR modelling showed a negative tendency in the overall effect of PFAS mixture on immune-health outcomes. Based on the stratified analysis, sex was suggested to be an effect modifier in the association of PFOS and atopic eczema. CONCLUSION: Our results contribute to the body of literature that observes the immunosuppressive effect of PFAS exposure during eczemas and allergies, both for PFASs individually and as a mixture.
Keywords: Male; Alkanesulfonic Acids; atopická dermatitida; Allergy; Prevalence; ekzém; Fluorocarbons; Bayesian kernel machine regression; Humans; Environmental Pollutants; Eczema; kyseliny alkansulfonové; Czech Republic; Česká republika; mužské pohlaví; prevalence; Female; tandemová hmotnostní spektrometrie; Perfluoroalkyl substances; Tandem Mass Spectrometry; ženské pohlaví; Bayesova věta; fluorokarbony; Hypersensitivity; Immune system; Dermatitis, Atopic; mladý dospělý; Young Adult; Longitudinal Studies; alergie; Adult cohort; látky znečišťující životní prostředí; longitudinální studie; lidé; dítě; Child; Bayes Theorem